Luke 3 : a commentary on the Gospel of Luke 19:28-24:53 - Bovon, François (Hermeneia--a critical and historical commentary on the Bible., 2012)
Francois Bovon's magisterial commentary on the Gospel of Luke is justly renowned for its combination of judicious historical and literary treatment of the Evangelist's context and for its theological sensitivity, informed by the wealth of the Christian interpretative tradition. Luke is clearly writing history in the manner of his Hellenistic and Jewish contemporaries, but Bovon insists he remains as well "a theologian of the Word of God." This volume completes the three-volume work (based upon Bovon's four volumes in the German EKK series) and represents the author's careful revision and updating of the German original.